Newborns' temperature submitted to radiant heat and to the Top Maternal device at birth - Rosemeire Sartori de Albuquerque; Corintio Mariani Neto; Ana Aparecida Sanches Bersusa; Vanessa Macedo Dias; Maria Izabel Mota da Silva
ABSTRACT Objective: to compare the axillar temperatures of newborns that are put immediately after birth in skin-to-skin contact under the Top Maternal device, as compared to those in a radiant heat crib. Methods: comparatives observational study of the case-control type about temperature of 60 babies born at the Obstetric Center and Normal Delivery Center of a public hospital of the municipality of Sao Paulo, being them: 29 receiving assistance in heated crib and 31 in skin-to skin contact, shielded by a cotton tissue placed on mother's thorax, called Top Maternal. Results: the temperature of the babies of the skin-to-skin contact group presented higher values in a larger share of the time measures verified, as compared to those that were placed in radiant heat crib, independently from the place of birth. Differences between the two groups were not statistically significant. Conclusion: the study contributes to generate new knowledge, supporting the idea of keeping babies with their mothers immediately after birth protected with the Maternal Top, without harming their wellbeing, as it keeps the axillar temperature in recommendable levels.